Dataset of occurrences and ecological traits of amphibians from Upper Paraguay River Basin, central South America - Neves, Matheus Oliveira; Cabral, Hugo [UNESP]; Pedrozo, Mariana; Ferreira, Vanda Lucia; Moura, Mario Ribeiro; Santana, Diego Jose (Pensoft Publishers, 2020)
There are many gaps in our biodiversity knowledge, especially in highly diverse regions such as the Neotropics. Basic information on species occurrence and traits are scattered throughout different literature sources, which makes it difficult to access data and ultimately delays advances in ecology, evolution, and conservation biology. We provide species occurrence and trait data for amphibian species in the Upper Paraguay River Basin, central South America. The compiled information is made available through two different datasets that hold (i) 17K species occurrence records and (ii) 30 species-level traits for 113 amphibian species. The first dataset includes the species occurrence records and informs specimen id, collection of housing, locality, geographical coordinates, geographic accuracy, collection date, and collector name. The second dataset covers species-level attributes on morphometry, diet, activity, habitat, and breeding strategy. These datasets improve accessibility to spatial and trait data for amphibian species in the Pantanal ecoregion, one of the largest wetlands on Earth.
Keywords: Anura; Datapaper; Gymnophiona; life history traits; Pantanal floodplain; wetland